Remaining faithful in ministry: 9 essential convictions for every pastor - MacArthur, John (Crossway, 2019)
He was convinced of the superiority of the new covenant -- He was convinced that ministry is a mercy -- He was convinced of the need for a pure heart -- He was convinced of the need to preach the word faithfully -- He was convinced the results belong to God -- He was convinced of his own insignificance -- He was convinced of the benefit of suffering -- He was convinced of the need for courage -- He was convinced that future glory is better than anything this world could offer.